Adoption Behaviour of Saffron Growers in Pashtun Zarghon of Herat Province in Afghanistan - Seddeqi, Khwaja Mohd. Shafi; Srivsatava , J. P.; Bose, Dipak Kr. (Indian Journal of Extension Education, 2015)
In Afghanistan, Saffron is one of the most important income and employment generating commercial crop, it occupies 700  hectares of land area. Saffron industry of the province is also improving the country's economy. Forty per cent of net  incomes of the nation come from saffron. Pashtun Zarghon distract of Herat province (Afghanistan) was purposively  selected for the present investigation covering 6 villages and 120 respondents selected randomly. The study inferred that  majority of respondents were of middle aged, illiterate, having joint family, larger family size, member of one  organization, medium level of annual income, medium socio-economic status, mass media exposure, regular radio  listener, TV viewer, occasional magazine reader, frequently participating in training programme and demonstration,  seldom participating in field visit, group meeting, tours have high level of knowledge but found to be ignorant about some  complex practices and to possess few adoption level as well. There was positive and significant correlation between  selected independent variable under study viz. age, education, annual income, mass media exposure, knowledge and  extent of adoption of saffron production technology.
Keywords: Adoption behaviour; knowledge; extent of adoption; saffron growers